DETERMINANTS OF BANK BUSINESS RISK ACCORDING TO RISK-BASED BANK RATING COMPONENTS APPROACH (A CASE IN COMMERCIAL BANKS THAT LISTED ON INDONESIA STOCK EXCHANGE) - Haryakusuma, Kurnia; Indrawati, Nur Khusniyah (Jurnal Ilmiah Mahasiswa FEB, 2016)
Banks    have  important  role  on  economy  of  Indonesia,  with  a  fully-regulated  principle,  Banking  Sectors  in  Indonesia  concern  to  keep  in  a  good performance  according  to  Indonesia  Bank  Rules  No.  13/1/PBI/2011  which emphasize on risk-based approach. Therefore, it is interesting to know the factors that  affect  commercial  banks’  business  risk  that  listed  on  Indonesia  Stock Exchange.  Those  factors  consist  of  risk  profile  (credit  risk,  liquidity  risk,  and interest  rate  risk), good corporate governance, earnings, and capital. The  sample used  in  this  researsh  are  26  commercial  banks  that  listed  on  Indonesia  Stock Exchange  during  research  period  since  2011-2013.  This  research  uses multiple linear  regression  analysis.  The  result  of  the  findings  are  credit  risk  has    effect against business  risk. While,  liquidity  risk does not have  effect  against business risk. Interest rate risk has effect against business risk. Good corporate governance does not have effect  against business risk. Earnings has  significant effect against business risk. Capital does not have effect against business risk. Hence, the  entire implication of the research  is commercial banks’ business risk is affected by three factors from risk-based bank rating (credit risk, interest rate risk, and earnings). Keywords: Risk-Based Bank Rating, Credit Risk,  Liquidity Risk,  Interest Rate Risk, Good Corporate Governance, Earnings, dan Capital, Bank’s business risk